Cyber ​​Extension: Information Technology and Agricultural Development - Asnamawati, Lina; Herawati, Is Eka; Yuliawati; Nurmalia, Ana (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Cyber ​​extension is an innovative approach in agricultural counseling that utilizes information and communication technology (ICT) to increase access and dissemination of information to farmers. With the development of digital technology, cyber extension allows farmers to get the latest information about agricultural practices, resource management, and market trends quickly and efficiently. This article discusses the role of cyber extension in agricultural development, including benefits such as improving farmers' skills, community empowerment, and efficiency in the counseling process. In addition, the challenges faced in implementation include accessibility of technology and digital literacy. By identifying opportunities for integrating new technology, cyber extension is expected to contribute to increasing the productivity and sustainability of the agricultural sector in the future.